Oyster population genetics : understanding natural populations and tracing introductions - Lapegue, Sylvie; Boudry, Pierre (World Aquaculture Society, Aquaculture 2006, 2006)
Oysters are among the most familiar of all marine invertebrate taxa. However our knowledge of oyster phylogeny and systematics is fragmentary. This is principally due to the plastic growth patterns of these animals, which result in a wide range of overlapping, ecophenotypic variants that greatly reduce the value of analysis based on shell morphology. Besides that, many intentional or accidental anthropogenic transfers have emphasised this situation. In several cases of misclassification or misidentification of oysters, DNA molecular data, have provided valuable new insights on the tracing of introductions or more generally on the phylogeographic relationships between oyster species. We will illustrate this issue with recent case studies from our lab on several flat and cupped oysters: (1) the Crassostrea gigas – Crassostrea angulata couple of Asian species and their successive introductions in Europe, (2) the new species of cupped oysters, Crassostrea honkongensis, described in Hong-Kong and very divergent from the species Crassostrea gigas it was initially supposed to be, (3) the mangrove oyster Crassostrea gasar that was shown not only to be present along the coasts of Western Africa but also along the Atlantic coasts of South America, and (4) the geographic disjunction between Ostreola stentina, described in the Mediterranean Sea, and the genetically closely related species Ostrea aupouria (from New Zealand) and Ostreola equestris (from Mexico Gulf/Atlantic). At the intra specific level, we will focus on one of the main documented case in Europe, the flat oyster, Ostrea edulis. It is a marine bivalve whose natural geographical distribution ranges along the European Atlantic coast from Norway to Morocco, in addition to the Mediterranean and Black Sea. Studies of allozymes, microsatellites and mitochondrial differentiation over the whole range concluded that a significant divergence existed between Mediterranean and Atlantic populations, together with an isolation-by-distance pattern. However, the average mitochondrial haplotypic diversity displayed a high among populations variance, reflecting smaller effective population size in some locations. Additionally, a ten-fold quantitative difference was observed in the same study in Fst between the mitochondrial and the nuclear genomes, which could be due to sex biased differential reproductive success between males and females. In order to further document this hypothesis, two experiments at the population level were conducted. First, brooding females were sampled in a wild population and the number of males fertilizing a given female estimated. Then, parentage analyses were achieved under experimental conditions: successive mass spawnings were collected from a population of potential genitors kept in hatchery, whose genotypes were known, in order to infer a posteriori the relative contribution of each genitor. Moreover, we aimed to better understand the reproduction dynamics of this species. Several patterns of spawning could be distinguished: unique, successive or extended in time. The different parental contributions and reproductive behaviors observed in these experiments are discussed in the context of the hypothesis of a variance in the reproductive success of males and females and consequences in local and temporal reduced effective population sizes.